Sosialisasi Hukum Pertanahan Sebagai Upaya Pengabdian Masyarakat Di Kelurahan Ngadirgo Kecamatan Mijen Kota Semarang: Socialization of Land Law as Community Service Efforts in Ngadirgo Village, Mijen District, Semarang City - Yulies Tiena Masriani; Suryoutomo, Markus; Saryana (Jurnal Suara Pengabdian 45, 2023)
Land is fixed, does not change, so that land has a promising investment value for most people, this is due to the tendency for the price or selling value of land to continue to increase. The need for housing for the community has increased the sale and purchase of land, the process of legality in land certification has become crucial and needs to be understood carefully. Actualization of community service through outreach regarding land law in Ngadirgo Village, Mijen District, Semarang City has the aim of increasing knowledge of understanding and knowing the importance of land registration and increasing knowledge of understanding and knowing the benefits and functions of land registration. The socialization uses power point presentation media by dividing the method into 4 main components, namely: the lecture method, the interactive discussion method, the consultation method, and the evaluation method. With the socialization related to land law, the people of Ngadirgo Village, Mijen Sub-District gained adequate insight and understanding so that later they can take care of land certification independently so as not to cause problems in the future. The land certificate bleaching program is also one of the main topics related to the socialization of land law as an effort to provide legal certainty and legal protection of community land rights based on the principles of simple, fast, smooth, safe, fair, equitable, and open and accountable so as to increase the welfare and prosperity of the community. and the country's economy as well as reducing and preventing land disputes and conflicts.